2021
DOI: 10.21203/rs.3.rs-275229/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decorin is an early CSF biomarker of Alzheimer’s Aβ amyloidosis

Abstract: Alzheimer’s disease (AD) is characterized by impaired protein homeostasis leading to amyloid-beta (Aβ) amyloidosis. Here, we show that autophagy is similarly inhibited in AD brains and App knock-in AD mouse models. To determine how pathologies translate to cerebrospinal fluid (CSF), label-free mass spectrometry of mouse CSF was used. This identified autophagy-related extracellular matrix (ECM) protein decorin as significantly and similarly increased in App knock-in mice and cognitively normal human subjects wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Recent researches have shown that it also plays a critical role in autoimmune and inflammatory diseases (Dong et al, 2022), antifibrotic (Järvinen and Ruoslahti, 2019), antioxidant, and antiangiogenic properties (Sofeu Feugaing et al, 2013;Järveläinen et al, 2015). DCN was found significantly increased in both AD mouse models and CSF of AD patients, predicting well innate immune activation and potential choroid plexus dysfunction (Jiang et al, 2022). Other studies also demonstrated that endothelial-activated DCNpositive astrocytes contributed to vascular amyloid deposits but not parenchymal amyloid plaques in AD mouse models and AD/CAA patients (Taylor et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Recent researches have shown that it also plays a critical role in autoimmune and inflammatory diseases (Dong et al, 2022), antifibrotic (Järvinen and Ruoslahti, 2019), antioxidant, and antiangiogenic properties (Sofeu Feugaing et al, 2013;Järveläinen et al, 2015). DCN was found significantly increased in both AD mouse models and CSF of AD patients, predicting well innate immune activation and potential choroid plexus dysfunction (Jiang et al, 2022). Other studies also demonstrated that endothelial-activated DCNpositive astrocytes contributed to vascular amyloid deposits but not parenchymal amyloid plaques in AD mouse models and AD/CAA patients (Taylor et al, 2022).…”
Section: Discussionmentioning
confidence: 94%